Consumer behavior research in the advent of the 21st century - Becker T.C. (Food quality products in the advent of the 21st century: production, demand and public policy, 2005)
A short overview on consumer behaviour research is provided followed by the evolvement of consumer behaviour as a scientific discipline. Subsequently, research on consumer behaviour towards food is discussed in greater detail whereby extensive reference is made to the progress of food consumption behaviour towards a scientific discipline. It is argued that agricultural economists are beginning to establish this new research field and are well suited to do so. The field of consumer behaviour towards food has to integrate physical sciences, psychology, economic sciences and social sciences. The research agenda for food consumption research is sketched and promising points are commented upon.
83. EAAE Seminar on Food Quality Products in the Advent of the 21st Century: Production, Demand and Public Policy, 2003/09/04-07, Chania (Greece)